Comparison of the Effectiveness of Murottal and Mujawwad Qur’anic Auditory Stimulus in Reducing Anxiety in Breast Cancer Patients: A Quasi-Experimental Study - Susanti, Risqi Wahyu; Kadar, Kusrini S; Bahar, Burhanuddin (Indonesian Journal of Cancer, 2025)
Background: Patients suffering from breast cancer have increased anxiety which must be addressed immediately because it will impact the patient’s quality of life. The auditory stimulus of the Qur’an is one of the therapies to reduce anxiety. This study aims to determine the difference in reducing anxiety using the Murottal Qur’an auditory stimulus compared to the Mujawwad Qur’an auditory stimulus in breast cancer patients. Method: This research uses a quasi-experimental design. A sample of thirty respondents was recruited using an accidental sampling technique. A total of 10 respondents listened to Murottal (medium tempo), 10 listened to Mujawwad (slow tempo) for 30 minutes each for 3 consecutive days and 10 were in the control group. Anxiety measurement using the State-Trait Anxiety Inventory (STAI) consists of state anxiety which was measured 24 hours before the intervention, the first day, the second day, and the third day after the intervention, and trait anxiety which was measured 24 hours before and the third day after the intervention. The Kruskal Wallis test was carried out to compare the decrease in anxiety.Results: The results of this study show that the auditory stimulus of the Qur’an using either Murottal or Mujawwad can reduce anxiety with a value of p = 000.Conclusion: This study concludes that there is no difference between Qu’an Murottal and Mujawwad auditory stimuli in reducing anxiety, but both tempos can reduce anxiety in breast cancer patients, so it is recommended for health workers to provide complementary treatment using Al-Qur’an auditory stimulus therapy to reduce breast cancer anxiety